al-Qarabah Baina al-Lughah al-Arabiyyah wa al-Lughah al-â€˜Ibriyyah Lughatain Samitain: Dirasah al-Lughah al-Muqaranah Baina Huruf al-Jar wa ×ž×™×œ×•×ª ×™×—×¡ (Milot Yakhats) - Asrina, Asrina; Ramadhan, Ilham (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aimed to describe the language kinship between Arabic and Hebrew as semitic languages when comparing ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± and ×ž×™×œ×•×ª ×™×—×¡ (milot yakhats). The question in this study addressed the similarities and differences between ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± in the Arabic language and Â ×ž×™×œ×•×ª ×™×—×¡ in the Hebrew language as semitic languages. The data source for the prepositions in the Arabic language rested upon â€œthe Noble Qurâ€™an, and the data source for the ×ž×™×œ×•×ª ×™×—×¡ in the Hebrew language relied on the book â€œ ×ª× â€×š (Tanakh). The data analysis was carried out using the comparative language approach. After analyzing the data, this study revealed that there are similarities and differences in the languagesâ€™ structures and meanings, indicating that the Arabic language and the Hebrew language are semitic languages. The similarities between ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± in the Arabic language and ×ž×™×œ×•×ª ×™×—×¡ in the Hebrew language can be found in the use of the noun after prepositions, and meanings if the ×ž×™×œ×•×ª ×™×—×¡ Â and the ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± used in the sentence. The differences between ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± in the Arabic language and ×ž×™×œ×•×ª ×™×—×¡ Â in the Hebrew language demonstrate that the Â ×ž×™×œ×•×ª ×™×—×¡ has many rules in its use, where the word afterwards affects its movement. Such a case does not exist in the Arabic language, and that ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± Â draws what follows itÂ  from the nouns, and this does not exist in the Hebrew language because it have no syntax. Subsequently, ×œ ×ž×™×œ×•×ª ×™×—×¡ Â Â and ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± have different meanings when used in sentences.